Thirty Years of China - U.S. Relations : Analytical Approaches and Contemporary Issues. - Guo, Sujian (Challenges facing Chinese political development., 2010)
This book examines structural factors, ideas, institutions, issues, and challenges that have shaped China-U.S. relations in the past thirty years, as well as the recent changes in the global geostrategic landscape and economic interdependence that have significant impacts on the bilateral relations into the 21st century.